Factory Layout Planning Using Activity Relationship Chart (ARC) and Activity Relationship Diagram (ARD) Method (Study Case: Kahuripan Foods Lembang) - Anisa Putri Rahmadani Lubis; Adelia Suyatno; Mohamad Faherza Hasyir Rahman; Septian Ade Isnanto; Vina Dwiyanti (Universitas Pendidikan Indonesia, 2022)
Kahuripan Food Lembang which is one of the SMEs (Small and Medium Industries) has invested in the food security sector of West Java. It is unfortunate that from the amount of potential owned by this industry, it does not have a factory layout according to The Indonesian Food and Drug Authority (BPOM) standards, thus hampering the production process. The method used in this research is a qualitative method with data collection techniques in the form of interviews, documentation, and observation. After obtaining the method to be used, then the layout is made with the selected method, namely the Activity Relationship Chart (ARC) and Activity Relationship Diagram (ARD) methods. Based on the results of the analysis and evaluation of the activity relationship of each department needed, it shows that the layout made can help streamline production and logistics activities because it has a flow of activities that have been adjusted to the degree of relationship as a basis for consideration and has been adjusted to the actual size needed.